INTERDEPENDENSI ANTARA INOVASI JASA, STRUKTUR OTONOMI, SISTEM PENILAIAN KINERJA DAN ORGANIZATIONAL OUTCOMES - Anastasia, Veronica; Purwanugraha, Heribertus Andre (KINERJA, 2003)
The purpose of this study is to examines: (1) positive relation between service innovation and structural autonomy, (2) positive relation between structural autonomy and financial performance measurement system, (3) positive relation between structural autonomy and nonfinancial performance measurement system, (4) indirect relation between sevice innovation and performance measurement system via structural autonomy, and (5) indirect relation between service innovation and organizational outcomes via strutural autonomy and performance measurement system. The responses of 100 top level managers and middle level managers, drawn from 14 hospitals of Daerah Istimewa Yogyakarta, to a questionnaire survey were analizysed by using a structural equation model.The findings from this study suggest that there’s a positive relation between service innovation and structural autonomy. If the hospital made a decision to running the new program, structural autonomy had to agree with the necessity of the implementation of that program. There’s a positive relation between structural autonomy and the both types of performance measurement system.. These measures will be influenced by the degree of autonomy delegated to the lower level of management.There’s an indirect relation between structural autonomy and performance measurement system through structural autonomy. Structural autonomy has an important role as mediator between service innovation and performance measurement system.There’s and indirect relation between service innovation and organizational outcomes through structural autonomy and performance measurement system.. The new program needs the right structural autonomy and design of performance measurement system, so that maximal outcomes can be achieved.Keywords: service innovation, structural autonomy, performance measurement system,organizational outcomes.